Skills Sought after in Business Communication Professionals - Ávila Rodríguez-de-Mier, Belén (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper describes the skills required of commercial communication professionals. The method used was descriptive documentary content analysis and the document analysed dealt with job offers with employment contracts at ESIC Business & Marketing School for the second half of 2019. A total of 438 offers were analysed. The demand for hybrid profiles is confirmed and the prominence of digital, content, analysis, social networks, web, SEM/SEO, English C1, advanced Excel, proactivity, ability to communicate and results orientation is observed.